3D fluid-solid coupling simulation for plate-type nuclear fuel assemblies under the irradiation condition. (August 2020) - Liao, Haoyu; Wang, Yangyang; Li, Yuanming; Wang, Kunpeng; Deng, Yangbin; Su, Min; Wu, Yingwei; Wang, Mingjun; Qiu, Suizheng
Abstract: In this study, a three-dimensional (3D) fluid-solid coupling simulation with the full consideration of irradiation effects for plate-type nuclear fuel assemblies was conducted. Mechanical models of radiation-induced deformations in solid domain and thermo-hydraulic models in fluid domain were established based on ABAQUS and FLUENT, respectively. By use of MpCCI, the capability of fluid-solid coupling simulation was developed through the real-time parameter exchange of different physical fields at fluid-solid boundary interfaces. The accuracy and reliability of fluid-solid coupling methodology by FLUENT-MpCCI-ABAQUS was validated through benchmark with simulation in public reference. The influence of radiation swelling and bending deformation on fluid thermal-hydraulic characteristics was investigated based on the developed coupling analysis method. In addition, the sensitivity study of heterogeneous swelling and flow channel width was carried out. The simulation result shows that radiation swelling and bending deformation exerted substantial influence on flow distribution and outlet temperature.